The Impact of Corporate Social Responsibility on the Investment Attractiveness of the Russian Companies - Kelchevskaya, Natalia Removna; Chernenko, Ilia Mikhaylovich; Popova, Ekaterina Vladimirovna (Economy of Regions, 2017)
Investigation of the impact of corporate social responsibility (CSR) and environmental responsibility on the economic performance over the past decades has shown that the implementation of CSR is one of the key drivers of value creation. Disclosure of social policy is one of the key CSR areas, it reduces information asymmetry and also contributes to the company’s reputation, decreasing uncertainty and risk in the assessment of the internal environment. This study shows that the disclosure of CSR information is able to increase the investment attractiveness of companies, and reduce the cost of equity. In the last decade, Russian industry has accumulated considerable positive experience in the implementing and positioning of corporate social responsibility (CSR) technologies, which has yet to be assessed. In this paper, we used the sample of social reports of 18 Russian companies in the period from 2004 to 2014. The authors provided content-analysis of information disclosure dimensions including staff training, social policy, charity and environmental responsibility. In contrast to other studies, the results show a comparatively moderate impact of disclosure on the cost of equity capital. Also, we found that different dimensions of the disclosure have an ambiguous impact on the investment attractiveness of companies. Our results allow formulating practical recommendations for the management of metallurgical, oil and gas Russian companies to increase their investment attractiveness, in particular, a prudent choice of CSR information for disclosure. The study is unique for the Russian practice of evaluating the effectiveness of CSR, as it is based on a sample of the largest industrial enterprises.